Numerical Investigation on heat transfer enhancement and entropy generation in a triangular ribbed-channel using nanofluid - N. Dahham, Mohammad; Ahmed, M. A. (Anbar Journal of Engineering Sciences, 2021)
In this paper, turbulent convective heat transfer in a triangular-ribbed chan-nel has been numerically investigated. SiO2-water with nanoparticles volume fraction of 4% and nanoparticles diameters of 30 nm is employed with Reyn-olds number ranging from 2000 to 8000. The governing continuity, momen-tum and energy equations in addition to low Reynolds number k-ε model have been transformed into body-fitted coordinates system and then solved using finite volume method. The effects of Reynolds number and rib heights on Nusselt number, pressure drop, thermal-hydraulic performance factor and entropy generation are presented and discussed. It is observed that the Nusselt number, pressure drop and thermal performance increase with in-creasing of Reynolds number and rib height. In addition, the highest perfor-mance factor can be obtained at Reynolds number of 6500 and rib height of 1.5 mm.